Catalyst for preparing piperazine and co-producing triethylene diamine from ethylenediamine and preparation method thereof
By modifying the β molecular sieve and spraying beryllium oxide on its surface, the problem of poor thermal conductivity of the catalyst is solved, the selectivity of piperazine and triethylenediamine and the life of the catalyst are improved, and more efficient reaction performance is achieved.
Patent Information
- Application Number
- CN202510025775.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
In the preparation of piperazine triethylenediamine for the existing catalysts, there are problems such as low conversion, poor selectivity, poor thermal conductivity and short service life in the preparation of piperazine triethylenediamine.
Modified β-molecular sieve is used as the active component, and beryllium nitrate is sprayed on the surface during the molding process. After high-temperature calcination and decomposition, beryllium oxide is formed to form a catalyst with good thermal conductivity.
It improves the selectivity of piperazine and triethylenediamine, extends the life of the catalyst, reduces the formation of carbon deposits, and can transport heat faster during the reaction, avoiding the catalyst overheating.
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, in particular to a catalyst for preparing piperazine and co-producing triethylenediamine from ethylenediamine and a preparation method thereof. Background Art
[0002] Piperazine is mainly used as a raw material for the production of drugs. It is an important intermediate. Piperazine can be used in the pharmaceutical industry to synthesize drugs such as norfloxacin and pipemidic acid. Piperazine derivatives can be used as surfactants, curing agents, emulsifiers and dispersants, etc. The main raw materials for synthesizing piperazine are: ethanolamine, N-β-hydroxyethylethylenediamine, diethylenetriamine, ethylenediamine, etc. Since ethylenediamine is cheap and easy to obtain, the reaction can be completed under normal pressure, which is more suitable for industrial production. When piperazine can be prepared by the self-condensation reaction of ethylenediamine, high-value triethylenediamine is produced as a by-product. The commonly used catalysts are molecular sieve catalysts or solid acid catalysts. Molecular sieve catalysts usually need to be modified. Different metal ion treatments have a great influence on the activity, stability, life and other properties of the catalyst. Molecular sieve catalysts mainly include A-type, X-type, Y-type and ZSM-5, etc., and are currently expanded to β molecular sieves and mordenite. β molecular sieve has three-dimensional twelve-membered ring macropores. The β molecular formula has more acidic centers, second only to ZSM-5 molecular sieve. The strength of the acidic centers of β molecular sieve does not change with the change of silicon-aluminum ratio, but the number of acidic sites increases with the increase of silicon-aluminum ratio. β molecular sieve has good thermal stability and anti-carbon deposition ability in catalytic reactions. β molecular sieve plays an important role in accelerating the diffusion of reactants and products because of its twelve-membered ring pores. It is very suitable for the highly exothermic reaction of preparing piperazine from ethylenediamine and producing triethylenediamine.
[0003] The existing method for preparing piperazine from ethylenediamine and co-producing triethylenediamine has the disadvantages of low conversion rate, poor selectivity, poor catalyst heat transfer effect and relatively short catalyst life.
[0004] Due to the high activity and strong adsorption of reactants and products, the carbon deposition and deactivation phenomenon on conventional molecular sieve catalysts in the system is relatively serious. A large amount of solvents, such as water, benzene, toluene, etc. and alcohols, are added to almost all ethylenediamine-catalyzed systems to facilitate the dispersion of reactants and products, inhibit the heat release of the system, delay the carbon deposition of the catalyst bed, and extend the catalyst life.
[0005] The preparation of piperazine from ethylenediamine and the co-production of triethylenediamine are highly exothermic reactions. The commonly used reactor is a fixed bed. Since the concentration of reactants is high at the bed inlet and the thermal conductivity of conventional catalysts is poor, the lower catalyst of the fixed bed heats up rapidly, which reduces the life of the lower catalyst. Using conventional catalysts, the maximum temperature difference in a fixed bed with a length of 2.5 meters can reach 80°C. Usually, the lower catalyst has been deactivated before the upper catalyst starts to react. Summary of the invention
[0006] 1. Problem to be solved: In view of the problem of poor thermal conductivity of the catalyst in the current molecular sieve catalyst reaction process, the present invention provides a catalyst for preparing piperazine and co-producing triethylenediamine from ethylenediamine, which has high selectivity in the reaction and good thermal conductivity. In addition, the present invention provides a method for preparing the above catalyst.
[0007] The invention discloses a catalyst for preparing piperazine and triethylenediamine from ethylenediamine and a preparation method thereof. The catalyst adopts beta molecular sieve as an active component, is subjected to metal modification, and sprays beryllium nitrate on the surface during the molding process. The catalyst is calcined at high temperature and decomposed to form beryllium oxide. The catalyst has high selectivity in catalyzing the reaction of preparing piperazine and triethylenediamine from ethylenediamine, and the product has good thermal conductivity, thereby extending the product life.
[0008] A catalyst for preparing piperazine from ethylenediamine and co-producing triethylenediamine comprises a molded matrix and beryllium oxide. The molded matrix is obtained by mixing a modified beta molecular sieve with a binder and water, and the beryllium oxide is coated on the surface of the molded matrix.
[0009] The coating thickness of the beryllium oxide on the surface of the molding substrate is 100-500nm.
[0010] The beryllium oxide is derived from beryllium nitrate, which is atomized and sprayed on the surface of the molding substrate in the form of an aqueous solution.
[0011] The mass ratio of beryllium nitrate to the molding matrix is: 0.005-0.05:
[0012] A further preferred range is 0.01-0.025:1.
[0013] The above-mentioned steps of preparing the catalyst for preparing piperazine and co-producing triethylenediamine from ethylenediamine include:
[0014] (1) β molecular sieve is used as an active component, a metal salt solution is added for impregnation, the impregnated material is washed and dried to obtain a modified molecular sieve, a binder and water are added to the modified molecular sieve, and the mixture is evenly mixed to prepare a slurry, which is then molded to obtain a molded matrix.
[0015] (2) Spraying beryllium nitrate: Take a certain amount of beryllium nitrate, add water, stir and mix to prepare a solution, and spray the solution on the formed substrate in step (1). The spraying thickness is determined by the spraying time and the concentration of the spraying liquid, and a beryllium nitrate coating of a certain thickness is formed on the surface.
[0016] (3) Decomposing beryllium nitrate to obtain beryllium oxide: The product obtained in step (2) is calcined at 600-750° C. for 0.5-6 h to decompose beryllium nitrate to obtain beryllium oxide, i.e., a catalyst product coated with beryllium oxide is obtained.
[0017] In step (1), the silicon-aluminum ratio of the beta molecular sieve is 30-100. As the silicon-aluminum ratio increases, the hydrothermal stability of the catalyst is better.
[0018] The metal salt in step (1) is a mixture of one or more of potassium nitrate, calcium nitrate, potassium acetate, calcium acetate, zinc acetate, and zinc nitrate, the molar ratio of the molecular sieve (based on the silicon dioxide contained) to the metal salt is 1:0.06-0.3, and the concentration of the metal salt solution (aqueous solution) is 0.2-1.5 mol / L. After metal modification, the hydrothermal stability of the molecular sieve catalyst is improved.
[0019] In step (1), the mass ratio of the modified molecular sieve powder to the binder is 1:0-2-0.8 (in terms of solid), and the solid content of the prepared slurry is 35%-50%. The binder is one or a mixture of two of silica sol, aluminum sol, and kaolin, and the binder here is a conventional binder for preparing catalysts.
[0020] In step (1), the molded substrate is not calcined. After the beryllium nitrate is sprayed, it is calcined. The high-temperature calcination decomposes the beryllium nitrate into beryllium oxide. At the same time, the bonding performance of the binder is utilized to form a firm spray layer of beryllium oxide on the molded substrate, and the overall catalyst is bonded more firmly.
[0021] In step (1), the molecular sieve and the binder are formed by spraying. For the microspheres formed by spraying, the recommended diameter range is the microsphere particle size D50 of 100-200 microns.
[0022] In step (2), the mass fraction of beryllium nitrate in the beryllium nitrate aqueous solution is 0.5-5%. The spraying method is atomization spraying, and the equipment that can be used can be a sugar coating machine, an atomizer, a sprayer, etc., and the spraying time is 10-60 minutes.
[0023] In step (2), under high temperature conditions, beryllium nitrate decomposes to obtain beryllium oxide, which is a good heat-resistant material. When covered on the surface of the microspheres, it can significantly improve the heat transfer efficiency of the internal medium of the final formed catalyst.
[0024] Beneficial effects of the present invention: The molecular sieve catalyst of the present invention uses beta molecular sieve as an active component, which has been modified with metal and has more suitable acidity, thereby improving the selectivity of piperazine and triethylenediamine.
[0025] The catalyst of the present invention is sprayed with beryllium oxide during the molding process. Beryllium oxide has a thermal conductivity of 200-250W / (mK), which is relatively high among oxides, and is inert. During the reaction of the catalyst, a large amount of heat released by the reaction can be transmitted more quickly, avoiding rapid passivation caused by overheating of the catalyst, reducing the generation of high molecular polymerized amine compounds due to excessive temperature of the catalyst, that is, reducing the generation of carbon deposits. Using this catalyst, the axial temperature difference of a 2-meter-high, 400-mm-diameter, internal-free reactor is less than 15°C, and the reaction performance is: the conversion rate is greater than 90%, and the piperazine selectivity is greater than 78%. DETAILED DESCRIPTION
[0026] The present invention is further described below by way of examples, but the present invention is not limited to the examples listed.
[0027] The following active component β molecular sieve comes from Tianjin Nanhua Catalyst Co., Ltd., the metal salt is an industrial product, the silica sol is an industrial product: the solid content is 25%, and the aluminum sol is an industrial product: the solid content is 22%.
[0028] Embodiment 1:
[0029] Step 1: Modification of β molecular sieve and preparation of forming matrix: The ratio of molecular sieve (in terms of silicon dioxide) to potassium nitrate is 1:0.1 (molar ratio). β molecular sieve (silicon-aluminum ratio 30) is added to the reactor, and potassium nitrate aqueous solution (concentration 0.5 mol / L) is added for impregnation. The impregnation time is 5 hours. After impregnation, the solution is filtered and washed, and dried into powder at 105°C to obtain modified β molecular sieve. Add silica sol to the modified molecular sieve powder, and the addition ratio is: modified molecular sieve powder: silica sol = 1:0.5 (mass ratio, in terms of solids). Add water to obtain slurry with a solid content of 40%. After rubber grinding, spray drying is performed to form microspheres with a D50 of 110 microns, which is the forming matrix.
[0030] Step 2: Spraying beryllium nitrate: the added amount is beryllium nitrate: formed substrate = 0.02:1 (mass ratio), beryllium nitrate is added to water to prepare a beryllium nitrate aqueous solution with a concentration of 2wt%, atomized in a sprayer, atomized into tiny droplets, which enter the catalyst agitator with the carrier gas, and the tiny droplets are sprayed on the surface of the formed substrate in step 1. Spraying for 20 minutes, after spraying, calcined at 650°C for 6 hours to obtain a catalyst, and the coating thickness of the catalyst measured by scanning electron microscope cross-section irradiation is 250-300nm.
[0031] Example 2
[0032] Step 1: Modification of β molecular sieve and preparation of forming matrix: The ratio of molecular sieve (in terms of silicon dioxide) to calcium acetate is 1:0.15 (molar ratio). β molecular sieve (silicon-aluminum ratio 80) is added to the reactor, and calcium acetate aqueous solution (concentration 1 mol / L) is added for impregnation. The impregnation time is 10 hours. After impregnation, the solution is filtered and washed, and dried to powder at 105°C. The modified molecular sieve powder is added with silica sol, and the addition ratio is: modified molecular sieve powder: silica sol = 1:0.7 (mass ratio, in terms of solids). Water is added to obtain a slurry with a solid content of 45%. After rubber grinding, it is spray-dried into microspheres with a D50 of 145 microns, which is the forming matrix.
[0033] Step 2: Spraying beryllium nitrate: the added amount is beryllium nitrate: molding substrate = 0.01:1, beryllium nitrate is added to water to prepare a beryllium nitrate aqueous solution with a mass fraction of 1wt%, atomized into tiny droplets by an atomizer, and sprayed onto the turning molding substrate. The spraying time is 15 minutes, and the catalyst is calcined at 600°C for 5 hours after spraying. The catalyst has a coating thickness of 150-200nm measured by scanning electron microscopy cross-section irradiation.
[0035] Example 3
[0036] Step 1: Modification of β molecular sieve and preparation of forming matrix: Feed ratio: The ratio of molecular sieve (calculated as silicon dioxide) to zinc nitrate is 1:0.08 (molar ratio), β molecular sieve (silicon aluminum ratio 60) is added to the reactor, and zinc nitrate aqueous solution (concentration 0.8 mol / L) is added for impregnation, and the impregnation time is 5 hours. After impregnation, the solution is filtered and washed, and dried to powder at 105°C. The modified molecular sieve powder is added with aluminum sol, and the addition ratio is: modified molecular sieve powder: aluminum sol = 1:0.4 (mass ratio, calculated as solid), and water is added to obtain slurry, the solid content of the slurry is 38%, and the microspheres are spray-dried after rubber grinding, and the D50 of the microspheres is 105 microns, which is the forming matrix.
[0037] Step 2: Spraying beryllium nitrate: the added amount is beryllium nitrate: molding substrate = 0.01:1 (mass ratio), beryllium nitrate is added to water to prepare a beryllium nitrate aqueous solution with a mass fraction of 0.08wt%, which is atomized into tiny droplets by an atomizer and sprayed onto the turning molding substrate. The spraying is carried out for 10 minutes, and after spraying, it is calcined at 680°C for 4 hours to obtain a catalyst. The coating thickness of the catalyst measured by scanning electron microscopy cross-section irradiation is 130-190nm.
[0038] Comparative Example 1:
[0039] Ca-modified ZSM-5 was used as the catalyst, and the reaction materials, temperature, space velocity and reactor form were the same as those in Example 4. The reaction conversion, piperazine and triethylenediamine selectivity are shown in Table 1. The axial temperature difference of the reactor was 58°C.
[0040] Comparative Example 2
[0041] The catalyst used was not sprayed with beryllium oxide, and the other compositions and preparation process were the same as those in Example 3, and the reaction materials, temperature, space velocity and reactor form were the same as those in Example 4. The reaction conversion, piperazine and triethylenediamine selectivity are shown in Table 1, and the reactor axial temperature difference was 67°C.
[0042] Example 4: Catalyst Evaluation
[0043] The microspheres obtained in Examples 1-3 and Comparative Examples 1-2 were extruded and then crushed into particles with a diameter of 4-6 mm for reaction evaluation. The material filling height in the reactor was 2 meters, the reaction raw material was a 40% aqueous solution of ethylenediamine, the reaction temperature was 350° C., the mass space velocity was 1 h-1, and the axial temperature difference of the reactor was less than 15° C. The reaction conversion rate, piperazine and triethylenediamine selectivity are shown in Table 1. The conversion rate is greater than 90%, and the piperazine selectivity is greater than 78%.
[0044] Table 1 Evaluation of reaction performance of examples and comparative examples
[0045] Ethylenediamine conversion rate / % Piperazine selectivity / % Triethylenediamine selectivity / % Example 1 90.5% 79.8% 15.5% Example 2 90.6% 78.2% 18.6% Example 3 91.1% 79.9% 18.3% Comparative Example 1 90.1% 78.2% 17.3% Comparative Example 2 90.9% 77.6% 13.3%
[0046] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A catalyst for preparing piperazine from ethylenediamine and co-producing triethylenediamine, characterized in that The catalyst comprises a molded matrix and beryllium oxide. The molded matrix is obtained by mixing the modified beta molecular sieve, a binder and water, and the beryllium oxide is coated on the surface of the molded matrix.
2. The catalyst for preparing piperazine from ethylenediamine according to claim 1, characterized in that Beryllium oxide comes from beryllium nitrate, which is applied to the surface of the molded substrate in the form of an aqueous solution.
3. The catalyst for preparing piperazine and triethylenediamine from ethylenediamine according to claim 2, characterized in that The mass ratio of beryllium nitrate to the molding matrix is: 0.005-0.05:
1.
4. The method for preparing a catalyst for preparing piperazine and triethylenediamine from ethylenediamine according to any one of claims 1 to 3, characterized in that: The preparation steps include the following: (1) using β molecular sieve as an active component, adding a metal salt solution for impregnation, washing and drying the impregnated material to obtain a modified molecular sieve, adding a binder and water to the modified molecular sieve and mixing them evenly to prepare a slurry, and then molding to obtain a molding matrix; (2) Spraying the formed substrate of step (1) with an aqueous solution of beryllium nitrate, and then calcining at 600-750° C. for 0.5-6 h to obtain a catalyst product.
5. The method for preparing a catalyst for preparing piperazine and co-producing triethylenediamine from ethylenediamine according to claim 4, characterized in that The silicon-aluminum ratio of the β molecular sieve in step (1) is 30-100.
6. The method for preparing a catalyst for preparing piperazine and co-producing triethylenediamine from ethylenediamine according to claim 4, characterized in that The metal salt in step (1) is one or more mixtures of potassium nitrate, calcium nitrate, potassium acetate, calcium acetate, zinc acetate, and zinc nitrate; the molar ratio of the molecular sieve to the metal salt is 1:0.06-0.3 based on silicon dioxide; and the concentration of the metal salt solution is 0.2-1.5 mol / L.
7. The method for preparing a catalyst for preparing piperazine and triethylenediamine from ethylenediamine according to claim 4, characterized in that The mass fraction of beryllium nitrate in the beryllium nitrate aqueous solution in step (2) is 0.5-5%.